Implementasi Konsep Merdeka Belajar dalam Pembelajaran Sejarah di SMA Negeri 19 Palembang - Esi Apriani; Alhadi Yan Putra; Nuril Furkan (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to describe and analyze the implementation of the concept of Merdeka Belajar in history learning at SMA Negeri 19 Palembang, the main focus of the study includes planning, implementation and learning outcomes as well as obstacles and efforts to overcome them. The concept of Merdeka Belajar provides freedom for students and teachers in choosing learning methods that suit their interests and potential. This study uses a qualitative approach with a descriptive method. Data collected through interviews, observations, and documentation. The results of the study show that the implementation of the concept of Merdeka Belajar at SMA Negeri 19 Palembang still faces various challenges, such as lack of facilities and infrastructure, limited teacher competence, and minimal innovation in learning methods. However, efforts to improve continue to be made through the development of innovative learning strategies, teacher training, and the use of technology in history learning. This study is expected to be a reference for the development of more interactive, contextual, and meaningful history learning for students in the era of modern education.